Reimagining the teaching of data - Pires, Flávia (2018)
In the near future, the level of digitalization of companies in the industrial sector, both in Portugal and in the world, will grow. The Industry 4.0, also called the fourth industrial revolution, focuses on the digitization of physical assets and their integration into the digital world, which in turn will produce a large amount of data. The implementation of this vision is already in motion, but it is strongly dependent on the skills that professionals have in the different dimensions of this multidisciplinary view. In the data dimension (Big Data), there is still a big gap in the labor market, in terms of professionals who know what to do with the data. This is one of the many professions that will be crucial to implementing the vision of Industry 4.0, being the analyst of large amounts of data, better known as Data Scientist. The Erasmus + DA.RE (Data Science Pathways to Re-imagine Education) project aims at the innovative development of a new mixed education program, acting as a catalyzer for the design and implementation of new educational programs at national, European and international level in the field of data science. The project aims to contribute to the reform of education, through the creation of a pilot course in the field of data science, overcoming the usual gap between higher education institutions and the business and industrial sectors. Taking into account several factors such as the demands of the labor market and the current academic situation will allow to create professionals in the area of data science.